Novel drug combinations suggested for treating pancreatic cancer - Elazar, Meyer (Technium BioChemMed, 2024)
Pancreatic cancer (PC) is a type of gastrointestinal tumor with poor anticipation and high level of death rate, being a fatal disease in which the overall 5-year survival rate is less than 4%1. PC poorly responds to most chemotherapeutic agents and the main current systemic chemotherapy treatments for patients with advanced disease are the drug combinations FOLFIRINOX and gemcitabine plus nanoparticle albumin-bound (nab)-paclitaxel (Abraxane). Therefore, there is a profound world-wide unmet medical need for new drug combination treatments having significant positive impact on the survival and day-to-day functioning of PC patients. It is suggested herein that treatment of drug combinations of bevacizumab plus bortezomib or dacarbazine and decitabine and optionally interferon α can be beneficial for patients suffering from locally advanced and metastatic PC, subject to creating predictive models to determine possible drug resistance and receiving positive results in clinical trials.